2022
DOI: 10.3390/pharmaceutics14081540
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PLGA Nanoparticles by Milling Spongelike PLGA Microspheres

Abstract: Currently, emulsification-templated nanoencapsulation techniques (e.g., nanoprecipitation) have been most frequently used to prepare poly-d,l-lactide-co-glycolide (PLGA) nanoparticles. This study aimed to explore a new top-down process to produce PLGA nanoparticles. The fundamental strategy was to prepare spongelike PLGA microspheres with a highly porous texture and then crush them into submicron-sized particles via wet milling. Therefore, an ethyl formate-based ammonolysis method was developed to encapsulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, the light microscope was utilized to see how microspheres' size altered throughout wet milling. 23 The morphological study using optical microscopy was done to determine how the microspheres' size and shape related to one another. The microscopy photos display spherical particles with what appears to be internal granulation, and they also demonstrated homogeneity in terms of morphology among many microsphere components.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the light microscope was utilized to see how microspheres' size altered throughout wet milling. 23 The morphological study using optical microscopy was done to determine how the microspheres' size and shape related to one another. The microscopy photos display spherical particles with what appears to be internal granulation, and they also demonstrated homogeneity in terms of morphology among many microsphere components.…”
Section: Methodsmentioning
confidence: 99%
“…PLGA nanoparticles (PLGA NPs) as drug carriers offer notable benefits in the pharmaceutical industry [3,4]. Numerous techniques have been employed for the synthesis of PLGA NPs, wherein the emulsification method is the most widely used preparation method [5,6]. The particle size of PLGA NPs produced through emulsificationsolvent evaporation is influenced by various factors, such as the emulsifier type and the volume ratio between the organic and aqueous phases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yuan [ 15 ] et al. prepared a curcumin-loaded microsphere using poly (lactic-co-glycolic acid) (PLGA) [ 16 , 17 ] as a shell material. The loading rate of curcumin by the microsphere is up to 48.78% ​± ​0.94, and the sustained release experiment in vitro showed that the microsphere is stably released within 40 days.…”
Section: Introductionmentioning
confidence: 99%